TERPAAN BERITA TENTANG CADAR DI MEDIA DAN INTERAKSI PEER GROUP TERHADAP SIKAP KEPADA WANITA BERCADAR - Lidya Dela Vega; Sunarto . (Interaksi Online, 2019)
Nowadays, the topic of the veil or niqab was rising. Media as a disseminator of information made some various reports about veil from positive tone news to negative tone news. Followed by that, the transition of various responses from the community began to reflect the dynamics of everyday life. From a positive attitude to the presence of a negative attitude that depends on the occasions, this attitude was do by individual or in groups. The purpose of this study was to study how much the effect of exposure to news about veil and peer group interaction towards society attitude to veil women .The study can be explained by social learning theory by Albert Bandura. This study was using probability sampling technique and multistage random sampling. The population in this study was the people of Semarang City who were expose the veil news around age 17-40 years old. Data analysis was using multiple linear regression. The results of this study show a hypothesis about the positive influence between news exposure about the veil and peer group interaction towards society attitude to veil women. With a strong level of adherence with 7,375 of significance and a large influence on exposure to the veil news and peer group interactions by 68% on people's attitudes.